EXPOSURE TO RADIATION WELDING WORKERS IN PT.PUTRA SULTRA SAMUDERA KENDARI AGAINST DISEASE DISORDERS CATARACT - Sya'ban, Abdul Rahim (YCAB Publisher & IAKMI SULTRA, 2015)
Background: In the industrial sector, the number of workers employed quite a lot, with the type and intensity of the various aspects of the environment including physical, chemical, biological and psychosocial. Various kinds of environments can cause a variety of occupational diseases.Aim: To determine the relationship between distance and time exposure PT. Putra Sultra Samudera Kendari against cataractsMethods: This research are a survey research with cross sectional analytic study, the data collection are done in a certain time to describe the condition of the populationResults: The results showed a strong relationship between the suitability of distance, time of exposure to diseases cataractsConclusions: There are a positive correlation and significant influence between the suitability of the distance and time of exposure with cataract disorder, the use of Personal Protective Equipment showed a positive relationship and did not have a significant effect on cataract disorders in workers in the welding parts firm PT. Putra Sultra Samudera Kendari.